Gambaran Sikap Perawat Tentang Pemakaian Alat Pelindung Diri di Ruang Rawat Inap Rumah Sakit TK II Udayana - Riski Suryaningsih; Elfi Kuswati (Bali Health Published Journal, 2022)
Background: The attitude of nurses in using personal protective equipment greatly influences the transmission of infection. The negative attitude in using personal protective equipment will result in work accidents such as being infected with a disease, this attitude has 22 times the risk of experiencing work accidents compared to the positive attitude of nurses. The purpose of this study was to describe the attitude of nurses about the use of personal protective equipment in the inpatient room of TK II Udayana Hospital. Methods: This study used a descriptive research design, with cross sectional approach. Sampling was simple random sampling with a total sample of 71 people, namely nurses who served in the Inpatient Room at TK II Udayana Hospital. The instrument used is a questionnaire in the form of a google form. Data were analyzed by univariate analysis. Results: The results of this study found that most of the respondents (95.8%) had a positive attitude about the use of personal protective equipment. Based on the characteristics of the respondents, namely the age characteristics, most of the respondents were 26 - 35 years old (47.2%), most of them were female (91.7%), the working period of most respondents was (79.2%). %) have a work period of three years or more than three years, most of them have a DIII Nursing education (55.6%), most of the respondents (83.3%) have received socialization / attended seminars / trainings. Conclusion: The attitude of nurses about the use of personal protective equipment in the Inpatient Room of TK II Udayana Hospital has mostly a positive attitude.